Development of Port Logistics Center: Bangladesh Perspective - Md ibrahim; Wang Xuefeng (International Journal of Engineering and Management Research, 2023)
Seaports as multi-dimensional transport node and integrated logistics center are the key components of the global transport system. Logistics and supply chain processes have high efficiencies in terms of increasing port performance. With regard to ports performance, an integrated port logistics center plays an important role in promoting economic development to absorb the value-added demand of local and international customers. Seaports are developing because of its multi-functions and multi-modalities, which focuses on expanding their services. This development of seaports allows them to cope with up growing demands of the trade. This publication presents subject matter concern with the development of seaports in Bangladesh as integrated logistics center. The objective of this research is to identify existing technological issues, challenges and impacts regarding the development of seaports as logistics centers in the maritime logistics system in Bangladesh. This study is a qualitative research and both primary and secondary data have been used. Based on the findings, some strategies and actions are suggested to the port authority; local logistics service providers and other stakeholders towards developing an efficient port logistics center in Bangladesh.